The role of VdSti1 in Verticillium dahliae: insights into pathogenicity and stress responses - Wu, Yutao; Zhou, Jinglong; Wei, Feng; Zhang, Yalin; Zhao, Lihong; Feng, Zili; Feng, Hongjie (Frontiers in microbiology, 2024)
Sti1/Hop, a stress-induced co-chaperone protein, serves as a crucial link between Hsp70 and Hsp90 during cellular stress responses. Despite its importance in stress defense mechanisms, the biological role of Sti1 in Verticillium dahliae, a destructive fungal pathogen, remains largely unexplored. This study focused on identifying and characterizing Sti1 homologues in V. dahliae by comparing them to those found in Saccharomyces cerevisiae . The results indicated that the VdSti1-deficient mutant displayed increased sensitivity to drugs targeting the ergosterol synthesis pathway, leading to a notable inhibition of ergosterol biosynthesis. Moreover, the mutant exhibited reduced production of microsclerotia and melanin, accompanied by decreased expression of microsclerotia and melanin-related genes VDH1, Vayg1, and VaflM. Additionally, the mutant’s conidia showed more severe damage under heat shock conditions and displayed growth defects under various stressors such as temperature, SDS, and CR stress, as well as increased sensitivity to H2O2, while osmotic stress did not impact its growth. Importantly, the VdSti1-deficient mutant demonstrated significantly diminished pathogenicity compared to the wild-type strain. This study sheds light on the functional conservation and divergence of Sti1 homologues in fungal biology and underscores the critical role of VdSti1 in microsclerotia development, stress response, and pathogenicity of V. dahliae .